Heterogenous Expression of Glycoprotein lb, IX and V in Platelets from Two Patients with Bernard-Soulier Syndrome Caused by Different Genetic Abnormalities - Noda, Masaaki; Fujimura, Kingo; Takafuta, Toshiro; Shimomura, Takeshi; Fujlmoto, Tetsuro; Yamamoto, Naomasa; Tanoue, Kenjiro; Arai, Morio; Suehiro, Akira; Kakishita, Eizo; Shimasaki, Akemi; Kuramoto, Atsushi (Thrombosis and Haemostasis, 1995)
Bernard-Soulier syndrome (BSS) is a rare inherited bleeding disorder, which is caused by deficiency or decrease of the platelet GPIb/IX/V complex. Analysis of two patients with BSS by How cytometry of the blood revealed different expression patterns of the components of the GPIb/IX/V complex. In case 1, GPIX was completely absent but residual amounts of GPIbα and GPV were detectable; in case 2, GPIbα was completely absent. We amplified the coding regions of GPIbα, GPIbß, GPV, and GPIX from the patients’ genomic DNA with the polymerase chain reaction (PCR) and sequenced the PCR products. In case 1, we identified a point mutation in the GPIX coding region that changes the codon for tryptophan-126 (TGG) to a nonsense codon (TGA). In case 2, we found a deletion of nucleotide within seven adenine repeats at the position of 1932 to 1938 in the coding region of GPIbα, which causes a frame shift that results in 58 altered amino acids and a premature stop codon. These genetic changes alter the transmembrane domain of GPIX or GPIbα and, therefore, would prevent proper insertion of the proteins in the plasma membrane. Thus, abnormality of a single component protein (GPIX or GPIbα) alters the assembly of the GPIb/IX/V complex and causes heterogenous surface expression of GPIbα, GPV and GPIX.